Modeling of Flood Inundation Due to the Overflow of the Bengawan Madiun River Using HEC-HMS and HEC-RAS 2D - Aviar Yusuf Affendi; Mahendra Andiek Maulana; Mohamad Bagus Ansori (Jurnal Teknologi dan Manajemen, 2026)
Bengawan Madiun is one of the main tributaries of the Bengawan Solo River, playing a critical role in the hydrological system of the Bengawan Solo Watershed. Limited river capacity, upstream land-use change, and increasing rainfall intensity have caused recurrent flooding in Ngawi Regency, particularly in Kwadungan and Pangkur Districts. A significant flood event occurred on 29 March 2025, inundating settlements, farmland, and infrastructure across the study area. This study aims to model flood inundation resulting from the overflow of the Bengawan Madiun River, evaluate model reliability, and analyze inundation characteristics under various return period discharge scenarios as a basis for flood mitigation recommendations. The average watershed rainfall of 72.80 mm was distributed into hourly rainfall using the Sri Harto method as input for HEC-HMS modeling. Calibration of the daily discharge model for the flood event of 29 March 2025 yielded an NSE of 0,85 and R² of 0,89, indicating that the model accurately represents the rainfall-runoff relationship of the Bengawan Madiun Watershed with a very high degree of accuracy. The HEC-RAS 2D simulation under existing conditions revealed a total inundation area of 6.329 km², concentrated in the lowland areas of Kwadungan and Pangkur Districts, with model validation yielding an RMSE of 0,03 m and NSE of 0,73. Return period discharge simulations demonstrated a consistent increase in inundation area from 1.654 km² at Q5 to 15.038 km² at Q50, with the 29 March 2025 flood event hydrologically identified as equivalent to a return period of 10 to 25 years. Based on these findings, river normalization and embankment construction along the critical segments of Bengawan Madiun are recommended as structural mitigation measures to significantly reduce flood inundation risk in Ngawi Regency.